Clinical Features and Functional Outcome of Patients with Non-compressive Myelopathy: A Hospital Based Cross Sectional Study from a Tertiary Care Center of Dhaka (Journal of Dhaka Medical College, 2025)
Background: Non-compressive myelopathy (NCM) has a wide temporal and clinical profile with etiology that varies over different geographical locations. The etiology may vary according to age, sex, geographical location and other associated factors. There remains a great deal of heterogeneity in clinical features and imaging findings. The functional outcome also differ according to etiology, extent of involvement and rapidity of the management.Aims: To evaluate the clinical features and functional outcome of patients with non-compressive myelopathy.Methods: This observational study was carried out in the Department of Neurology, Neurosurgery and Medicine of Dhaka Medical College Hospital, Dhaka, during January2018 to December 2019. A total of 84 patients suffering from non-compressive myelopathy were included in this study. Age >18 years, both male and female patients with features of myelopathy admitted within 14 days of onset were enrolled in this study and followed up for 180 days.Results: 40 (47.5%) patients had acute transeverse myelitis (ATM) without spinal shock followed by 26(30.9%) had ATM with spinal shock, 9(10.8%) had multiple sclerosis (MS), 6(7.2%) had neuromyelitis optica (NMO) and 3(3.6%) had neuromyelitis optica specterum disorders (NMOSD). More than one third (38.2%) patients belonged to age 18-20 years followed by 22(26.3%) in 21- 30 years, 20 (23.9%) in 31-40 years, 6(7.2%) in 41-50 years and 4(4.8%) in >50 years. Male to female ratio was almost 2:1. Almost two third (63.1%) patients had paraplegia and 31(36.9%) had quadriplegia. Three fourth (75.0%) patients had sudden onset and 21(25.0%) had insidious onset. More than three fourth (84.5%) patients had sensory involvement. Two third (65.5%) patients had bowel and bladder involvement. The mean Modified Rankin Scale (MRS) score on admission was 4.3±0.86 and 3.13±1.15 at 180 days. The difference was statistically significant (p